Respuesta :

Answer:

m(arc EFD) = 270°

Step-by-step explanation:

m(arc EFD) = m(arc EF) + m(arc FD)

Since, m(arc EF) = Angle subtended by the arc EF at the center

                           = 146°

m(arc DE) = 90°

And sum of all the angles subtended by the arcs at the center = 360°

m(arc EF) + m(arc FD) + m(arc DE) = 360°

146° + m(arc FD) + 90° = 360°

m(arc FD) = 360° - 236°

m(arc FD) = 124°

Therefore, m(arc EFD) = m(arc EF) + m(arc FD)

                                     = 146 + 124

                                     = 270°

Answer:

270°

Step-by-step explanation: